Redescription of Ploiaria mellea (Heteroptera: Reduviidae: Emesinae) and its first report from India - Boyane, Swapnil S.; Ghate, Hemant V. (Zootaxa, 2020)
A macropterous species, Ploiaria mellea McAtee & Malloch, 1926 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Leistarchini) is reported for the first time from India; the previously unknown male is illustrated and described. The species was originally described from the Philippines. Since the species was found in three climatically different localities near Pune, it must be a well-established emesine bug that has so far remained undetected or unidentified in India.